Cromoglycate, not ketotifen, ameliorated the injured effect of warm ischemia/reperfusion in rat liver: role of mast cell degranulation, oxidative stress, proinflammatory cytokine, and inducible nitric oxide synthase - El-Shitany NA; El-Desoky K (Dove Medical Press, 2015)
Nagla A El-Shitany,1,2 Karema El-Desoky3 1Department of Pharmacology and Toxicology, Faculty of Pharmacy, King Abdulaziz University, Jeddah, Saudi Arabia; 2Department of Pharmacology and Toxicology, Faculty of Pharmacy, Tanta University, Tanta, Egypt; 3Department of Pathology, Faculty of Medicine, Tanta University, Tanta, Egypt Abstract: Hepatic ischemia/reperfusion (ISCH/REP) is a major clinical problem that is considered to be the most common cause of postoperative liver failure. Recently, mast cells have been proposed to play an important role in the pathophysiology of ISCH/REP in many organs. In contrast, the role played by mast cells during ISCH/REP-induced liver damage has remained an issue of debate. This study aimed to investigate the protective role of mast cells in order to search for an effective therapeutic agent that could protect against fatal ISCH/REP-induced liver damage. A model of warm ISCH/REP was induced in the liver of rats. Four groups of rats were used in this study: Group I: SHAM (normal saline, intravenously [iv]); Group II: ISCH/REP; Group III: sodium cromoglycate + ISCH/REP (CROM + ISCH/REP), and Group IV: ketotifen (KET) + ISCH/REP (KET + ISCH/REP). Liver damage was assessed both histopathologically and biochemically. Mast cell degranulation was assessed histochemically. Lipid peroxidation (malondialdehyde [MDA]) as well as the levels of glutathione (GSH), interleukin-6 (IL-6), and tumor necrosis factor alpha (TNF-α), the formation of nitric oxide (NO), and the expression of inducible NO synthase (iNOS) were determined. The results of this study revealed increased mast cell degranulation in the liver during the acute phase of ISCH/REP. Moreover, CROM, but not KET, decreased the activity of alanine aminotransferase, aspartate aminotransferase, and lactic dehydrogenase and maintained normal liver tissue histology. Both CROM and KET protected against mast cell degranulation in the liver. In addition, both CROM and KET decreased IL-6 and TNF-α. However, CROM, but not KET, decreased MDA formation and increased GSH. Furthermore, KET, but not CROM, increased both NO formation and iNOS expression. In conclusion, this study clearly demonstrated mast cell degranulation in warm ISCH/REP in the liver of rats. More importantly, CROM, but not KET, ameliorated the effect of ISCH/REP-induced injury in rat liver. CROM may protect the liver through mast cell stabilization, inhibition of TNF-α, IL-6, MDA, and iNOS and increased GSH. KET may maintain ISCH/REP-induced liver injury through the NO/iNOS pathway. Keywords: ischemia/reperfusion, mast cells, liver, sodium cromoglycate, ketotifen, nitric oxide, inducible nitric oxide synthase